Chapter California City (real estate) and California City (wonderland) - Minami, Noritaka (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
This photographic art project examines contemporary embodied activity and urban development in California City, California outside of Los Angeles. The photographs critique the notion of development and the kinds of embodied livelihood it supports according to the cultural imagination of wonder and real estate.